Efficient Combination of G‐C3N4 and CDs for Enhanced Photocatalytic Performance: A Review of Synthesis, Strategies, and Applications. Issue 48 (8th March 2021) - Ai, Lin; Shi, Run; Yang, Jie; Zhang, Kan; Zhang, Tierui; Lu, Siyu
Abstract: Recently, heterogeneous photocatalysts have achieved much interest on account of their great potential applications in resolving many tough energy and environmental troubles around the world through an ecologically sustainable way. Heterogeneous nanocomposites composed of graphitic carbon nitride (g‐C3 N4 ) and carbon dots (CDs) possess broad spectrum absorption, appropriate electronic band structures, rapid carrier mobility, abundant reserves, excellent chemical stability, and facile synthesis methods, which make them promising composite photocatalysts for suitable applications such as photocatalytic solar fuels production and contaminant decomposition. With the rapid development in photocatalysis by hybridization of g‐C3 N4 and CDs, a systematic summary and prospection of performance improvement are urgent and meaningful. This review first focuses on various kinds of effectively synthetic methods of composites. Following, the strategies available for enhanced performance, including morphology optimization, spectral absorption improvement, ternary or quaternary composition hybrid, lateral or vertical heterostructures construction, heteroatom doping, and so forth, are fully discussed. Then, the applications mainly in efficient photocatalytic hydrogen generation, photocatalytic carbon dioxide reduction, and organic pollutants degradation are systematically demonstrated. Finally, the remaining issues and prospect of further development are proposed as some kind of guidance for powerful combination of g‐C3 N4 and CDs with high efficiency to photocatalysis. Abstract : This review summarizes the recent progress of heterogeneous photocatalysts of g‐C3 N4 /carbon dot (CD)‐based nanocomposites and their applications mainly in efficient catalytic hydrogen generation, photocatalytic carbon dioxide reduction, and organic pollutants degradation. Finally, the challenges and opportunities for g‐C3 N4 /CD‐based photocatalysts are critically discussed to offer insight of this field.